2012
DOI: 10.1093/brain/aws047
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA 486 is a potentially novel target for the treatment of spinal cord injury

Abstract: MicroRNAs have been shown to effectively regulate gene expression at the translational level. Recently, we identified novel microRNAs that were upregulated in a mouse model of spinal cord injury. Among those, we have focused on microRNA 486, which directly represses NeuroD6 expression through a conserved sequence in its untranslated region. We correlated the overexpression of microRNA 486 in motor neurons with a poor outcome due to progressive neurodegeneration and a pathophysiology that is mediated by reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 35 publications
2
76
1
Order By: Relevance
“…These results suggest that miR20a is a potential target for therapeutic intervention following SCI. Traumatic injury induces miR-486 upregulation in a murine model of spinal cord injury (72). Additionally, miR-486 is significantly increased by the accumulation of reactive oxygen species (ROS) in vitro and in vivo.…”
Section: Traumatic Injurymentioning
confidence: 99%
“…These results suggest that miR20a is a potential target for therapeutic intervention following SCI. Traumatic injury induces miR-486 upregulation in a murine model of spinal cord injury (72). Additionally, miR-486 is significantly increased by the accumulation of reactive oxygen species (ROS) in vitro and in vivo.…”
Section: Traumatic Injurymentioning
confidence: 99%
“…Another study revealed that some mRNAs of inflammatory mediators, such as intercellular adhesion molecule 1 (ICAM-1), interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α), were potential targets of miR-181a, miR-411, miR-99a, miR-34a, miR-30c, miR-384-5p and miR-30b-5p 16, miR-486 17, which were down-regulated post-SCI, and miR-17 and miR-20 31, miR-124a 36, which were up-regulated post-SCI, and miR-124a, which was down-regulated at 1 and 7 days post-SCI 36. On the other hand, some mRNAs of anti-inflammatory mediators, such as TRAF6, annexin A1 and A2, were likely targets of miR-146a 31, 32, miR-223 31, 36, miR-221 16 and miR-1 16, 32, which were up-regulated post-SCI, and miR-1, which was down-regulated at 3 days post-SCI 31, 36.…”
Section: Introductionmentioning
confidence: 99%
“…The SCI model was established as previously described (20). Briefly, the mice were anesthetized by intraperitoneally injection with 10% chloral hydrate (30 mg/kg).…”
Section: Methodsmentioning
confidence: 99%